ASSESSMENT OF THE BENEFITS DERIVED BY AGRIC-YES PARTICIPANTS ON INTEGRATED FISH FARMING IN LAGOS STATE, NIGERIA - Lawal, A.A. (Nigerian Journal of Fisheries, 2021)
This study assessed the benefits derived by participants of Agric-YES on IFF in Lagos State, Nigeria. A simple random sampling technique was used in selecting 20% (120) of the 600 registered participants. A primary research approach was used for data collection from the respondents with the aid of a structured questionnaire. The data were analyzed using descriptive and inferential analytical techniques. The major limitations of the scheme include the use of local farm tools, non-availability of modern technologies, inadequate availability of trainers, unavailability of start-up capital, and lack of access to credit facilities. The major benefits of the scheme are employment generation and increased income. The majority of the participants agreed that IFF ensures optimal utilization of available resources (88.3%), requires high-level experience (80.8%), uneasy to manage (75.8%), cost-effective (75.8%), and labour intensive (73.3%). Inferential analysis shows that there is no significant relationship between socio-economic characteristics and benefits derived except secondary occupation (χ² = 47.578, p = 0.001), household size (r = 0.381, p = 0.001) had positive and significant relationship while age (r = -0.188, p = 0.040) which has a negative and significant relationship with benefit derived from the programme. The result of this study revealed that the majority of the participants involved in the empowerment scheme for integrated fish farming age range was equally within the economically active range of less than 25- 30.